Occurrence of cardiometabolic diseases in elderly attended at a reference center in Belém – PA (Research, Society and Development, 2021)
This study aims to identify the predominance of Systemic Arterial Hypertension (HAS), Diabetes Mellitus (DM) and Dyslipidemia (DLP) in elderly patients, relating to gender and senior group. This is a cross-sectional, observational and descriptive-statistical study, established on the investigation of medical records of 470 elderly people, of both genders, being monitored at an outpatient secondary care referral center in Belém - PA. Patients whose medical records had inconclusive data were excluded from the study. A collection form was applied, made by the authors themselves, with information about gender, age and presence of HAS, DM and DLP. Statistical analysis was performed using the Statistical Package for the Social Sciences program. To confirm the connection in the middle of HAS, DM and DLP and the independent variables sex and age, the chi-square test of adherence was registered. It was detected that of the 470 individuals, 76.2% were female and 23.8% were male. Age ranged from 60 to 117 years, with an average of 76.65. The occurrence of HAS was 56.2%; of DM2, 20.2%; and for DLP, 19.78%. Reached from the results obtained, it is observed that the prevalence of HAS, DM and DLP is significant in the aged, regardless of gender. Thus, considering that cardiovascular diseases are a frequent cause of death, it is extremely important to encourage policies to prevent and control these diseases.